Managing the Selenium Content in Soils in Semiarid Environments through the Recycling of Organic Matter - R. Garcia Moreno; R. Burdock; María Cruz Díaz Álvarez; J. W. Crawford (Applied and Environmental Soil Science)
Around 30% of the world’s population suffers from either a lack of one or more essential micronutrients, or the overconsumption of these minerals, which causes toxicity. Selenium (Se) is a particularly important micronutrient component of the diet with a well-documented and wide-ranging role in maintaining health. However, this important micronutrient can be lacking because soil and crop management are focused on high yields to the detriment of the quality of crops required to ensure a healthy human diet. Currently around 15% of the global population has selenium deficiency. This paper focuses on Se availability in semiarid soils and how micronutrients can be effectively managed through the recycling of organic matter. Because many mineral reserves are being exploited unsustainably, we review the advantages of using organic by-products for the management of the biofortification of Se in crops. This type of practice is particularly useful in arid and semiarid environments because organic matter acts as a reservoir for Se, preventing bioaccumulation and leaching. There are also potential local economic benefits from using organic by-products, such as manures and sewage sludge.